Characterization of Physicochemical Properties of Degraded Inceptisol and Growth Performance of Barangan Banana (Musa paradisiaca L.) - Dimas Candra Dwi Saputtra; Priyono Prawito; Winaldy Rahmadan Habibil; Heru Widiyono; Fahrurrozi Fahrurrozi (TERRA : Journal of Land Restoration, 2025)
This study evaluated the physicochemical characteristics of degraded Inceptisol and the growth performance of Barangan banana (Musa paradisiaca L.) under two soil management systems—tillage and no-till—in Seluma, Bengkulu Province, Indonesia. Field observations were conducted on a 25 ha banana plantation, with soil samples collected at depths of 0–15 cm and 15–30 cm. Plant growth measurements were taken from two representative plants per plot. Data were analyzed using a randomized complete block design (RCBD), followed by Duncan’s Multiple Range Test (DMRT) at α = 0.05. Tillage significantly improved several soil properties, including bulk density, aggregate stability, and nutrient availability. Tilled plots exhibited greater aggregate stability, higher cation exchange capacity (CEC), and increased exchangeable K and available P. The surface layer (0–15 cm) also contained higher total nitrogen and available nutrients compared with deeper soil. For plant responses, tillage enhanced plant height and pseudostem girth, suggesting better soil structure and nutrient uptake, whereas no-till plots produced more leaves. Overall, moderate tillage improved soil physical quality and nutrient dynamics in degraded Inceptisol, thereby supporting superior vegetative growth of Barangan banana. Full text pdf